2016
DOI: 10.1016/j.jacc.2016.09.943
|View full text |Cite
|
Sign up to set email alerts
|

Later Onset Fabry Disease, Cardiac Damage Progress in Silence

Abstract: Significant cardiomyocyte substrate accumulation in IVS4 patients led to severe and irreversible cardiac fibrosis before development of LVH or other significant cardiac manifestations. Thus, it might be too late to start enzyme replacement therapy after the occurrence of LVH or other significant cardiac manifestations in patients with later onset FD. This study also indicated the importance of newborn screening for early detection of the insidious, ongoing, irreversible cardiac damage in patients with later on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…The cardiac phenotype in FD has been increasingly understood by cardiovascular magnetic resonance (CMR) over the past 15 years. Early data showed the presence of late gadolinium enhancement (LGE) in approximately 50% of patients, initially in the basal inferolateral wall in FD (11), sometimes occurring before LVH in females (12) or in some mutations in males (13). Recent advances in CMR allow quantitative assessment of the myocardium using fundamental magnetic tissue relaxation constants, for example T1, which are displayed as parametric color maps.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac phenotype in FD has been increasingly understood by cardiovascular magnetic resonance (CMR) over the past 15 years. Early data showed the presence of late gadolinium enhancement (LGE) in approximately 50% of patients, initially in the basal inferolateral wall in FD (11), sometimes occurring before LVH in females (12) or in some mutations in males (13). Recent advances in CMR allow quantitative assessment of the myocardium using fundamental magnetic tissue relaxation constants, for example T1, which are displayed as parametric color maps.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings also suggest that female patients with LVH might show LGE more frequently than male patients with LVH. Recent reports have suggested that LGE appears without LVH particularly in female Fabry patients [19,20]. Although all of our patients with LGE already had LVH, female patients had milder LVH than male patients, possibly reflecting the earlier presentation of LGE in female patients than in male patients.…”
Section: Discussionmentioning
confidence: 47%
“…In the case of later-onset phenotypes, the monitoring procedures should be focused on the affected organ (ie, heart) and its periodicity should be determined case by case. 56 In children diagnosed with pathogenic GLA variants responsible for later-onset phenotype, through either screening protocols or cascade genetic testing within families, particular attention should be given to appropriate genetic counselling and the delivery of detailed information on the natural course of this form. Because later-onset FD often become overt only in adulthood, patient monitoring should be adapted and unnecessary procedures and treatment avoided.…”
Section: Baseline Clinical Work-up and Subsequent Monitoringmentioning
confidence: 99%